Factors influencing the abundance of predatory orius species (Heteroptera: Anthocoridae) in the landscape - Veres, Andrea; Kotán, Attila; Fetykó, Kinga; Orosz, Szilvia; Szalai, Márk; Otto, Stefan; Bohan, David; Lavigne, Claire; Tóth, Ferenc (JOURNAL OF LANDSCAPE ECOLOGY, 2012)
Introduction of Orius predators is an efficient tool to control thrips species (western flower thrips, Frankliniella occidentalis, onion thrips, Thrips tabaci) in greenhouse sweet pepper. However, indigenous Orius species living in the surroundings can colonize greenhouses spontaneously. In our study we aimed to investigate the factors, that might influence the abundance of Orius species in the landscape. We hypothesized that Orius adults do not occur randomly in the landscape, and if so, the abundance is higher in adjustment to seminatural areas. Furthermore, we carried out a methodology study, which confirmed that sampling of poison hemlock (Conium maculatum L.) is a suitable method to estimate Orius abundance at landscape scale. We found O. niger to be dissociated to semi-natural areas in the extremely hot study year, and was aggregated in other part of the landscape. Our results and literature data suggest that although it overwinters in seminatural areas, it spreads out to cultivated areas in the growing season, and profit there from high amount of their resources. O. niger might be relevant for biological control especially in hot seasons and in greenhouses surrounded by extensive arable fields.
Keywords: habitat; GIS; greenhouse sweet pepper; thrips; conservation biological control